2014
DOI: 10.1016/j.ophtha.2013.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal Aflibercept Injection for Macular Edema Resulting from Central Retinal Vein Occlusion

Abstract: Treatment with intravitreal aflibercept provided significant functional and anatomic benefits after 52 weeks as compared with sham. The improvements achieved after 6 monthly doses at week 24 largely were maintained until week 52 with as-needed dosing. Intravitreal aflibercept generally was well tolerated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
255
6
18

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 254 publications
(300 citation statements)
references
References 12 publications
(26 reference statements)
21
255
6
18
Order By: Relevance
“…These results were also mirrored by the GALILEO study that showed 18-letter improvements by 24 weeks that dropped to 16.9 letters at the end of the first year and 13.7 letters at 76 weeks. 18 In addition, 80% of patients had no fluid on OCT at week 24 compared with 60.2% at 76 weeks. This deterioration in visual acuity in both studies can be explained by the extended duration of follow-ups in studies.…”
Section: Afliberceptmentioning
confidence: 98%
See 1 more Smart Citation
“…These results were also mirrored by the GALILEO study that showed 18-letter improvements by 24 weeks that dropped to 16.9 letters at the end of the first year and 13.7 letters at 76 weeks. 18 In addition, 80% of patients had no fluid on OCT at week 24 compared with 60.2% at 76 weeks. This deterioration in visual acuity in both studies can be explained by the extended duration of follow-ups in studies.…”
Section: Afliberceptmentioning
confidence: 98%
“…17,18 A summary of the major aflibercept trials as well as a comparison with CRUISE, SCORE, and GENEVA is summarized in Table 2. It can be difficult to compare data between different trials, especially if baseline criteria and primary/secondary end points are different.…”
Section: Afliberceptmentioning
confidence: 99%
“…Aflibercept received FDA approval in November 2011 for AMD, September 2012 for RVO, July 2014 for DME, and March 2015 for diabetic retinopathy. Aflibercept has been proven in large, randomized clinical trials for treating AMD in VIEW1 and 2 (Heier et al 2012), CRVO in GALILEO (Korobelnik et al 2014), BRVO in VIBRANT (Campochiaro et al 2015), and DME in DA VINCI (Do et al 2012).…”
Section: Rvomentioning
confidence: 99%
“…Laser photocoagulation was the standard therapy for patients with ME secondary to BRVO, but it was not found to have benefit in patients with ME secondary to CRVO [6,7]. More recently, studies have shown benefit of steroid implantation and anti-Vascular Endothelial Growth Factor (anti-VEGF) therapies for the management of patients with ME secondary to RVO [8][9][10].…”
Section: Introductionmentioning
confidence: 99%